Physiotherapists' Experiences Using the Ekso Bionic Exoskeleton with Patients in a Neurological Rehabilitation Hospital: A Qualitative Study. (8th January 2020) - Read, Emily; Woolsey, Cora; McGibbon, Chris A.; O'Connell, Colleen
Abstract : Use of bionic overground exoskeletons to assist with neurological rehabilitation is becoming increasingly prevalent and has important implications for physiotherapists and their patients. Yet, there is a paucity of research about the impact of integrating this technology on physiotherapists' work. The purpose of this study was to explore how the training and implementation of using the Ekso robotic exoskeleton with patients affects physiotherapists' work. An exploratory qualitative study of three physiotherapists working at a neurological rehabilitation centre in Eastern Canada was conducted using one-on-one semistructured interviews in July 2017. Audio recordings were transcribed verbatim, and data was coded and analyzed using thematic analysis. Six themes emerged from the data: developing organizational capacity; ethical use of technology; benefits of the equipment; challenges of the equipment; cognitive workload; and the technological environment. The results suggest that the adoption and integration of bionic exoskeletons into rehabilitation practice is not as simple as training physiotherapists and giving them the device. More research is needed to understand the increased cognitive demands of working with patients using technologically advanced exoskeletons within a dynamic, technology-rich healthcare environment, while managing patient expectations and ethical use.